2012
DOI: 10.1007/s00127-012-0568-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial risk factors associated with fathers’ mental health in the postnatal period: results from a population-based study

Abstract: These findings provide new information to guide the assessment of fathers' risk for psychological distress in postnatal period. There are also important social policy implications related to workplace entitlements and the provision of services for fathers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 39 publications
5
74
2
3
Order By: Relevance
“…Our earlier work established an association between poor job quality and postpartum psychological distress for mothers and fathers (3,52). This is consistent with other studies reporting associations between poor job quality and the mental health of fathers of dependent children (29,(53)(54)(55), but most do not disaggregate fathers in the postpartum or early parenting period specifically.…”
Section: The Work-family Interfacesupporting
confidence: 83%
See 1 more Smart Citation
“…Our earlier work established an association between poor job quality and postpartum psychological distress for mothers and fathers (3,52). This is consistent with other studies reporting associations between poor job quality and the mental health of fathers of dependent children (29,(53)(54)(55), but most do not disaggregate fathers in the postpartum or early parenting period specifically.…”
Section: The Work-family Interfacesupporting
confidence: 83%
“…Risk factors for father's mental health difficulties include a history of depression, having a partner with poor mental health, a poor quality intimate relationship, and concerns regarding their competence in the parenting role (2,3). As most fathers remain fully engaged in employment during the postpartum period, job-related pressures may also determine their mental health.…”
Section: Introductionmentioning
confidence: 96%
“…As far as we know, this is one of the first studies in the U.S. to find workplace policies related to fathers' mental health across the transition to parenthood. Giallo and colleagues (2013), in an Australian sample of over 3,000 new fathers in the first year of parenthood, found that fathers with the lowest job quality, meaning less access to: 1) control of work hours and work load, 2) job security, and 3) paid family leave had five time the odds of reporting psychological distress than fathers with high job quality. In our findings, mothers' leave time, but not fathers', predicted declines in paternal anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Both adolescent mothers [8, 9] and fathers [10] are susceptible to postpartum depression due to low social support or social isolation. Evidence has also demonstrated (although among older adults) that maternal [11, 12] and paternal [13] depression or psychological distress after the child's birth is associated with low parenting competence and low parenting self-efficacy.…”
Section: Introductionmentioning
confidence: 99%